Efektivitas Media Kartu Visual terhadap Peningkatan Kosakata Literasi Dasar Siswa Kelas Rendah: Sebuah Studi Literatur (Periode 2022-2026) - Komariah, Komariah; Sumartiningsih, Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Background: The low mastery of basic literacy vocabulary among Phase A students (1st Grade) represents a critical challenge during the preschool transition period. This transition frequently encounters cognitive obstacles that necessitate immediate solutions. The Magical Flash Card media emerges as an innovation to address basic literacy limitations through a concrete approach. Objective: This study aims to analyze the effectiveness of visual card media, specifically the